2011
DOI: 10.1680/feng.2011.164.4.189
|View full text |Cite
|
Sign up to set email alerts
|

Confidential reporting on structural safety

Abstract: The Confidential Reporting on Structural Safety scheme was established in 2005 by the Standing Committee on Structural Safety to collect, analyse and publish personal reports about failures and the safety of structures. The objective is to learn from the experiences of engineers and help to prevent future failures. Names of authors are confidential and identifying features from event descriptions are removed. A panel of experts provides commentary on the lessons that can be learned, and the reports and comment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A second potential source is the Confidential Reporting Scheme on Structural Safety (Cross) (see http://www.crossstructural-safety.org) which is the subject of the third paper in this issue (Soane, 2011). This paper provides a comprehensive review of the scheme, its outputs to date, and the international interest shown.…”
mentioning
confidence: 99%
“…A second potential source is the Confidential Reporting Scheme on Structural Safety (Cross) (see http://www.crossstructural-safety.org) which is the subject of the third paper in this issue (Soane, 2011). This paper provides a comprehensive review of the scheme, its outputs to date, and the international interest shown.…”
mentioning
confidence: 99%